Lower Viral Loads and Slower CD4+ T-Cell Count Decline in MRKAd5 HIV-1 Vaccinees Expressing Disease-Susceptible HLA-B*58:02 - Leitman, Ellen M.; Hurst, Jacob; Mori, Masahiko; Kublin, James; Ndung'u, Thumbi; Walker, Bruce D.; Carlson, Jonathan M.; Gray, Glenda E.; Matthews, Philippa C.; Frahm, Nicole; Goulder, Philip J.R. (The Journal of infectious diseases, 2016)
Background. HLA strongly influences human immunodeficiency virus type 1 (HIV-1) disease progression. A major contributory mechanism is via the particular HLA-presented HIV-1 epitopes that are recognized by CD8+ T-cells. Different populations vary considerably in the HLA alleles expressed. We investigated the HLA-specific impact of the MRKAd5 HIV-1 Gag/Pol/Nef vaccine in a subset of the infected Phambili cohort in whom the disease-susceptible HLA-B*58:02 is highly prevalent. Methods. Viral loads, CD4+ T-cell counts, and enzyme-linked immunospot assay–determined anti-HIV-1 CD8+ T-cell responses for a subset of infected antiretroviral-naive Phambili participants, selected according to sample availability, were analyzed. Results. Among those expressing disease-susceptible HLA-B*58:02, vaccinees had a lower chronic viral set point than placebo recipients (median, 7240 vs 122 500 copies/mL; P = .01), a 0.76 log10 lower longitudinal viremia level (P = .01), and slower progression to a CD4+ T-cell count of <350 cells/mm3 (P = .02). These differences were accompanied by a higher Gag-specific breadth (4.5 vs 1 responses; P = .04) and magnitude (2300 vs 70 spot-forming cells/106peripheral blood mononuclear cells; P = .06) in vaccinees versus placebo recipients. Conclusions. In addition to the known enhancement of HIV-1 acquisition resulting from the MRKAd5 HIV-1 vaccine, these findings in a nonrandomized subset of enrollees show an HLA-specific vaccine effect on the time to CD4+ T-cell count decline and viremia level after infection and the potential for vaccines to differentially alter disease outcome according to population HLA composition. Clinical Trials Registration. NCT00413725, DOH-27-0207-1539.